2018
DOI: 10.21873/cgp.20110
|View full text |Cite
|
Sign up to set email alerts
|

Human Periprostatic Adipose Tissue: Secretome from Patients With Prostate Cancer or Benign Prostate Hyperplasia

Abstract: Background/Aim: Periprostatic adipose tissue (PPAT) directs tumour behaviour. Microenvironment secretome provides information related to its biology. This study was performed to identify secreted proteins by PPAT, from both prostate cancer and benign prostate hyperplasia (BPH) patients. Patients and Methods: Liquid chromatography-mass spectrometry-based proteomic analysis was performed in PPAT-conditioned media (CM) from patients with prostate cancer (CMs-T) (stage T3: CM-T3, stage T2: CM-T2) or benign disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…Adipogenesis, as defined by the formation of adipocytes from stem cells [ 1 ], and the adipose tissue itself have drawn much attention at the onset of chronic inflammation in metabolic diseases, such as type 2 diabetes mellitus, cardiovascular diseases, and in several types of cancer [ 2 , 3 ]. Among the processes involved in the setting of these diseases, the adipose tissue secretome has been inferred to play a crucial paracrine regulatory role in brain cancer [ 4 ], prostate cancer [ 5 ], bladder cancer [ 6 ], breast cancer [ 7 ], and colon cancer [ 8 ]. Molecular links between central obesity and breast cancer have also been inferred to trigger oncogenic signaling pathways, including NFκB, JAK, STAT3, and AKT [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adipogenesis, as defined by the formation of adipocytes from stem cells [ 1 ], and the adipose tissue itself have drawn much attention at the onset of chronic inflammation in metabolic diseases, such as type 2 diabetes mellitus, cardiovascular diseases, and in several types of cancer [ 2 , 3 ]. Among the processes involved in the setting of these diseases, the adipose tissue secretome has been inferred to play a crucial paracrine regulatory role in brain cancer [ 4 ], prostate cancer [ 5 ], bladder cancer [ 6 ], breast cancer [ 7 ], and colon cancer [ 8 ]. Molecular links between central obesity and breast cancer have also been inferred to trigger oncogenic signaling pathways, including NFκB, JAK, STAT3, and AKT [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pertinent to the endocrine nature of the AT, PPAT adipocytes and stromovascular cells secrete a myriad of adipokines capable of modulating PCa behavior, probably under the instruction of PCa cells [ 147 , 148 , 149 ]. Indeed, profound alterations in the PPAT epigenome, transcriptome, and secretome have been shown in lean and obese patients with benign prostatic hypertrophy (BPH), non-aggressive, and aggressive PCa [ 150 , 151 , 152 , 153 ]. Importantly, proliferative and metabolic pathways were differentially regulated according to the stage of disease [ 150 , 151 ].…”
Section: Periprostatic Adipose Tissue Secretome and Prostate Cancer P...mentioning
confidence: 99%
“…Also, Ribeiro et al (2012) revealed that PPAT produces MMPs that degrade the prostatic ECM facilitating tumoral dissemination and progression into metastatic PCa. Therefore, targeting signaling pathways and secreted factors within the PPAT could be useful in limiting PCa advancement ( Sacca et al, 2019 ).…”
Section: Stromal-derived Mediators Of Inflammation In Pcamentioning
confidence: 99%